KEKERASAN BERBASIS GENDER PADA MASA COVID-19 DI INDIA - Maharani, Annisa Bintang; Olivia, Yessi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
This research explains the increasing number of gender-based violence (GBV) cases in India during the COVID-19 pandemic. The Indian government employed lockdown policy to anticipate the spread of the virus. Gender-based violence cases in India have increased due to the lockdown policies implemented by the Indian government, which have trapped women with perpetrators of gender-based violence. This research aims to understand why gender-based violence in India increased during COVID-19. It uses the theoretical framework of the Relationship Between Gender-Based Violence and Crisis Situations and applies a qualitative research method, with document analysis techniques complemented by a literature review, utilizing secondary data gathered from various sources such as books, journals, bulletins, newspapers, annual reports from related agencies, documents, or other materials that support the research. During the pandemic, cases of gender-based violence (GBV) in India increased due to lockdown policies that forced victims to stay longer with their abusers without access to protection. Victims became more vulnerable, isolated, and had difficulty obtaining help. Additionally, other factors such as economic instability, rising unemployment, and psychological stress due to the lockdown further worsened conditions, increasing the risk of domestic conflict and leading to a surge in gender-based violence cases. The lockdown also isolated victims from social support, making them more vulnerable to escalating physical and psychological abuse. Keywords: Gender-based Violence, COVID-19, India, Lockdown, Pandemic.